1980
DOI: 10.1254/jjp.30.449
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of nitroglycerin, trimetazidine, verapamil and SK&F 24260 on venous return as revealed by the open-loop method in the dog.

Abstract: Abstract-To obtain detailed information concerning the effects of different vaso dilators on venous return, experiments were carried out on 28 dogs by the use of the open-loop method. Blood from the superior and inferior venae cavae was drained at the level of the tricuspid valve into a reservoir, from which blood was pumped into the right atrium at a constant flow rate. Changes in reservoir volume reflected a total blood shift from the experimental dog and indicated changes in venous return. Drugs were admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Even verapamil, whose cardiodepressant action became manifest in vasodilator doses and which only reduced venous return and CO in closed-loop preparations [17], increased venous return in open-loop preparations of dogs in which the cardiac input was controlled, when administered into the ascending aorta so as to minimize the effects on the heart [22]. We ascribed the decreased venous return and CO produced by the highest doses of cromakalim and pinacidil to decreased cardiac contractility.…”
Section: Discussionmentioning
confidence: 93%
“…Even verapamil, whose cardiodepressant action became manifest in vasodilator doses and which only reduced venous return and CO in closed-loop preparations [17], increased venous return in open-loop preparations of dogs in which the cardiac input was controlled, when administered into the ascending aorta so as to minimize the effects on the heart [22]. We ascribed the decreased venous return and CO produced by the highest doses of cromakalim and pinacidil to decreased cardiac contractility.…”
Section: Discussionmentioning
confidence: 93%
“…Firts. trimetazidine inhibits the ischemia-induced al terations, because it decreases the oxygen consumption of the heart as a result of a decrease in venous return to the heart [Jmai et al, 1977;Taira et al, 1980], In the present study, however, we did not measure the oxy gen consumption of the heart, and therefore it is uncertain whether or not this view is cor rect. However, according to the hemody namic data of the present study, trimetazidine did not have a marked effect on blood pressure and heart rate, suggesting that trimetazidine may not have a marked influence on the oxygen consumption of the heart.…”
Section: Discussionmentioning
confidence: 73%
“…Mean circulatory filling pressure is a measure of total body venous tone (Guyton et al, 1973). An increase in venous return after verapamil (Taira et al, 1980) or nifedipine (Ogilvie, 1985) has also been reported to occur in anaethetised dogs. The suggestion that anipamil caused an increase in cardiac output by increasing venous tone is supported by other reports to the effect that a number of calcium antagonists can increase cardiac output while reducing heart rate (Hof et al, 1982;Flaim & Zelis, 1982).…”
Section: Discussionmentioning
confidence: 91%